O cuidado de enfermagem em saúde mental frente a gravidez na adolescência: revisão sistemática de literatura - RÊGO, Ícaro Genniges (2020)
Adolescence is a very important period in the formation of an individual, which often affects psychosocial issues and directly interferes with physical and mental health, such as teenage pregnancy and emotional issues that may occur in individuals without family, social structure. and health. Adolescent health is a theme allowed by several dilemmas, applied manuals dealing with adolescent mental health are non-existent, or the professional nurse in face of this reality has no guides to allow their exercise of care. Therefore, this study sought through a systematic review of literature articles that shows which nursing care was performed in view of the mental health of pregnant adolescents. As a result, the nursing practices performed are adapted for consultations and mental health questionnaires of pregnant adult women, or that make it difficult to bond professionals and users and cause gaps for a humanized and complete care.